Expression of nucleolin, nucleophosmin, upstream binding transcription factor genes and propolis in wound models. (1st October 2022) - Kaya, Murat; Eroz, Recep; Kabakliogli, Murat
Abstract : Objective: Nucleolar proteins have important functions in the regulation of cell homeostasis and play a crucial role in sensing various types of stress, such as genotoxic stress. Propolis has epithelial, analgesic, antibacterial, antifungal and antiviral effects. This study aimed to evaluate the gene expression levels of nucleolar proteins: nucleolin (NCL); nucleophosmin (NPM1); and upstream binding transcription factor (UBTF), as well as the benefits of propolis in wound healing. Method: This experimental study was conducted by creating clean and clean–contaminated wounds according to the Surgical Site Infection Guidelines, 2016. A total of seven animal groups were included in the study: control; laparotomy; anastomosis; fucidic acid with/without anastomosis; propolis with/without anastomosis Results: Statistically significant differences of levels of gene expression among the groups were detected for NCL (p=0.004), NPM1 (p=0.011) and UBTF (p=0.000). When the expression levels of the related genes and blood parameters are considered, the relationship between NCL, NPM1 and UBTF expression levels and blood parameters (NE, EO, NE(%), LY, LY(%), EO, EO(%), MO, MO(%), RBC, HB, HCT, MCV, MCHC, RDW, RDW(%), PLT, PDW and PCT) were statistically significant. Conclusion: The nucleolar proteins such as NCL, NPM1 and UBTF have important functions in cell viability and its maintenance under various condition such as stress and injury. Additionally, propolis has positive benefits in wound healing and in the prevention of wound infection. Our findings provide the first insights into the putative role of those proteins in wound healing.